Multidimensional realizations of individual motivations in historical forms of socio-cultural organization - Радзівілл, Олександр Анатолійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
Stable organization forms of communities participant as «Nations» in different historical ages was assigned. Law of Nations was considered as system of regulation of different social-relations levels making us macro fluctuations of typical individual motivation. To show the historically withstand forms of organization of human collectives as the incarnate of constants of psychophysically nature of human is the aim of this article. The historical type forms of social organization were incarnated in the concrete public order by means of legalization of naturally-legal motivations of individuals belong to different age, ethnic, corporate or another social groups. The collective subjects of historical process are generalized by an author in six ideal forms. Three of them incarnate the microscale of social organization, elementary collectives: gens (clans), territorial communities, corporations. Three of them are the most associations typical for the appointed historical epoch macroscale of social organization: there are «gens-tribe societies»; «societies of regional civilization builders» and «civil societies». Three elementary forms differ in inter se both time of appearance and combination in them genetic and corporate system making factors. Genetic factors operate trans historically as well as corporate factors are more historically late, and basic sense of post-Neolithic history of mankind consisted in opening and embodiment of more new, large and complex forms of social and cultural integration. Primitive clan was the only form of compact residence of mankind and settlement him on the surface of planet during the first half of its history. It was also the only subject of international relations in their widest understanding. Human’s socially-legal ideas verbalizing and reflecting repeatedly in the process of interfamily relations during a few ten thousands of years formed a "primitive family right". Basic historical heritage of "primitive family right" is steady harmony of natural man and women rights consolidated on the deep levels of human consciousness and on their basis also general harmony of all other aspects of social organization. During the second half of its history mankind began to form more and more composite kind of commonwealth. Appear of the early specialized collectives became the beginning of this process. Absolute power of man fastened for the first time in history in early shepherd clans. A Matriarchy reigns in just time in early agricultural communes. The professional corporation sand more composite social educations were formed on the base of the early stationary communes. Both the agricultural communes and corporations were organized by another principle than primitive clan. Corporate factors are determinative for them though the genetic factors are also remaining. Specifically, on the neighborliness based solidarity of agricultural communes, as well as base of corporative solidarity were sacral norms and principles of transmission of professional knowledge and skills. Large macroscales societies as «units of historical research» were distinguished by A.Toynbee. Developing his ideas it is possible to admit successive appearance to history of three their kinds: «primitive (gens-tribe) societies» that exist a few ten thousands of years; «societies of regional civilization builders» that appeared near six or seven thousands years ago and «civil societies» that is formed during four last centuries. The appeal of «civil society» is related to such phenomena of new time as parliamentarianism, constitutionalism, universal elective right, state-nation, protection of human rights, international public law.